1989
DOI: 10.2208/jscej.1989.410_113
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Analyses of Concrete Structures by the Modified Distinct Element Method

Abstract: A new method for analyzing the fracture of concrete structures is proposed in which concrete is considered a granular assembly. Because concrete is a complex, extremely heterogeneous material, it is difficult to analyze it's failure properties by the Finite Element Method (FEM) in which concrete is considered a homogeneous, continuous medium. We have developed a Modified Distinct Element Method (MDEM) that can be applied to the problems of fracture of concrete structures. In the MDEM the respective major const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…The slab is thus modeled as a continuous material with an elastic-brittle constitutive behavior. Yet, similar to what is classically done for concrete (Meguro and Hakuno, 1989;Kusano et al, 1992;Camborde et al, 2000;Hentz et al, 2004), the response of this layer to the dynamic propagation of failure in the WL is also computed with the DE method. In that case, however, the considered elements (grains of size r) have no physical meaning and should only be regarded as entities of discretization similar to the mesh size in FE models.…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…The slab is thus modeled as a continuous material with an elastic-brittle constitutive behavior. Yet, similar to what is classically done for concrete (Meguro and Hakuno, 1989;Kusano et al, 1992;Camborde et al, 2000;Hentz et al, 2004), the response of this layer to the dynamic propagation of failure in the WL is also computed with the DE method. In that case, however, the considered elements (grains of size r) have no physical meaning and should only be regarded as entities of discretization similar to the mesh size in FE models.…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…For a two-dimensional analysis, potential element shapes are [5,3,4], Meguro and Hakuno [13], and Thornton [20] in their respective studies. Ting et al [21] employed elliptical elements for their studies of granular materials.…”
Section: Choice Of Element Shapementioning
confidence: 99%
“…Since then, it has been extensively used in analyzing failure in discontinuous media. Thornton and Kafui [20] employed a DE model to study the breakup of agglomerates of circular and spherical particles, while Meguro and Hakuno [13] used a similar model to study the fracture of concrete structures. Trent [22] developed a DE model to study wave propagation through granular materials.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the method for determining the various parameters in the DEM are given in Meguro and Hakuno (1989). The parameters for the ground model used in this study are shown in Table 1.…”
Section: Parametersmentioning
confidence: 99%